The role of a "Schottky barrier" at an electron-collection electrode in solid-state dye-sensitized solar cells - Snaith, H; Gratzel, M (2006)
The role of Schottky barrier at an electron-collection electrode in solid state dye-sensitized solar cells was investigated. A compact TiO2 layer was inserted between the fluorine-doped tin-oxide (FTO) anode and the nanoporous TiO2 in order to reduce loss through recombination between holes in the hole transporter and electrons in the FTO. An apparent positive shift in the conduction band was observed under UV illumination, which results in improving electron injection from the lowest unoccupied molecular orbital (LUMO) energy level of the dye molecules into the TiO2 conduction band, or into newly created states. It was demonstrates that a Schottky barrier exists at the FTO/TiO2 interface when a TiO2 compact layers is used between the FTO and the nanoporous film. Incorporation of an oxygen-rich compact layer in a solid state dye-sensitized solar cell is found to be improving the device performance.